Inhibition of Chitosan Ice Coating on the Quality Deterioration of Quick-Frozen Fish Balls during Repeated Freeze–Thaw Cycles - Lixin Chang; Ying Li; Xue Bai; Xiufang Xia; Weidong Xu (Foods, 2023)
Chitosan ice coating’s properties and its inhibitory effect on the quality deterioration of quick-frozen fish balls during repeated freeze–thaw cycles were investigated. When the chitosan (CH) coating concentration increased, the viscosity and ice coating rate increased, while water vapor permeability (WVP), water solubility, and transmittance decreased, and 1.5% CH was regarded as the excellent coating to apply to freeze–thaw quick-frozen fish balls. As the freeze–thaw cycles increased, the frost production, total volatile base nitrogen (TVB-N) values, and free water content of all of the samples increased significantly (p < 0.05), and the whiteness values, textural properties, and water-holding capacity (WHC) decreased. Freeze–thaw cycles expanded the aperture between the muscle fibers and the occurrence of crystallization and recrystallization between cells increased, damaging the original intact tissue structure, which were confirmed by SEM and optical microscopy. Compared with the untreated ones, the frost production, free water, and TVB-N of the samples with 1.5% CH decreased during 1, 3, 5, and 7 cycles, and were reduced by 23.80%, 32.21%, 30.33%, and 52.10% by the 7th cycle. The WHC and texture properties showed an increasing trend during the freeze–thaw cycles. Therefore, the chitosan ice coating effectively inhibited the quality deterioration by reducing water loss, the occurrence of ice crystallization and recrystallization, and the pores of the samples.